Total electron content in the Martian atmosphere: A critical assessment of the Mars Express MARSIS data sets. Issue 3 (9th March 2015) - Sánchez‐Cano, B.; Morgan, D. D.; Witasse, O.; Radicella, S. M.; Herraiz, M.; Orosei, R.; Cartacci, M.; Cicchetti, A.; Noschese, R.; Kofman, W.; Grima, C.; Mouginot, J.; et al.
Abstract The total electron content (TEC) is one of the most useful parameters to evaluate the behavior of the Martian ionosphere because it contains information on the total amount of free electrons, the main component of the Martian ionospheric plasma. The Mars Express Mars Advanced Radar for Subsurface and Ionosphere Sounding (MARSIS) radar is able to derive TEC from both of its operation modes: (1) the active ionospheric sounding (AIS) mode and (2) the subsurface mode. TEC estimates from the subsurface sounding mode can be computed from the same raw data independently using different algorithms, which should yield similar results. Significant differences on the dayside, however, have been found from two of the algorithms. Moreover, both algorithms seem also to disagree with the TEC results from the AIS mode. This paper gives a critical, quantitative, and independent assessment of these discrepancies and indicates the possible uncertainty of these databases. In addition, a comparison between the results given by the empirical model of the Martian ionosphere developed by Sánchez‐Cano et al. (2013) and the different data sets has been performed. The main result is that for solar zenith angles higher than 75°, where the maximum plasma frequency is typically small compared with the radar frequencies, the two subsurface algorithms can be confidently used. For solar zenith angles less than 75°, where the maximum plasma frequency is very close to the radar frequencies, both algorithms suffer limitations. Nevertheless, despite the solar zenith angle restrictions, the dayside TEC of one of the two algorithms is consistent with the modeled TEC.